A case for true morphological crypsis: Pacific Dasya anastomosans and Atlantic D. cryptica sp. nov. (Dasyaceae, Rhodophyta). Issue 4 (1st July 2017) - Schneider, Craig W.; Quach, Phong K.; Lane, Christopher E.
Abstract: With the advent of regular genetic bar coding for taxonomic distinction a decade ago, descriptions of morphologically cryptic species have exploded in the macroalgal literature. A review of this literature is provided. Produced by either convergence of morphological characteristics by geographically distant species or divergence of species from a common ancestor, cryptic species can often be distinguished by subtle anatomical or reproductive features. Some species pairs, however, remain indistinguishable with overlapping characteristics even upon close inspection. Such a case is demonstrated for two species differentiated by sequences of a portion of the rbc L chloroplast gene: Dasya anastomosans from the Indo-Pacific and D. cryptica sp. nov . from the western Atlantic. After assembling morphological and anatomical data for the two species, no significant differences were detected between them, thus affording the usage of the epithet for the new species from an ocean basin more distant than its congener.